Češki stavki z zaimkom to v vlogi osebka in njihovi slovenski ustrezniki - Stankovska, Petra (Jezik in slovstvo, 2025)
The common mistakes that are made by speakers of a certain language when acquiring a specific second language can point to phenomena that are different and thus of interest in the two languages. One of the widespread mistakes of Slovenians when learning Czech is the omission of the pronoun to ("it", "this" or "that") in the subject position, and vice versa. Czechs tend to add this pronoun to Slovene sentences as well, even though it is superfluous in them or even not necessary. In this paper, we will analyse different types of sentences in which the demonstrative pronoun in the subject position is syntactically necessary in Czech, but is not used in Slovenian (e.g.:Je to výborné – Odlično je.).
Keywords: Czech; češčina; demonstrative pronomen; kazalni zaimek; osebek; sentence; Slovenian; slovenščina; stavek; subject